The story of a story: the Grigoriu Theatre Company - ILIE, Oana (Studia Universitatis Babeș-Bolyai Dramatica, 2018)
At the beginning of the past century, tenor Constantin Grigoriu began gathering the outstanding members of the Romanian Lyrical Company, historically re-labelled „The Grigoriu Company” as an homage to its founder. Even if all its years of assiduous activity seem few when compared to the grand scale of time’s passing, the Grigoriu Company’s two decades of existence have left a mark upon the history of artistic life in Romania. This was due, in part, to its self-assumed status of „competitor” of the National Theatre, aiming to offer its regionally diverse public an alternative form of entertainment. Grigoriu also discovered and promoted grandiose performers the likes of Nicolae Leonard, Velimir Maximilian, Ciucurette, Carussy, Florica Florescu. The company contributed to the formation of an extraordinary generation of vaudeville singers too: Florica Cristoforeanu, Elena Drăgulinescu-Stinghe and Virginia Miciora were some of the most talented Romanian lyrical performers.